(untitled) (Medical Forum Monthly, 2024)
Objective: To evaluate association of microalbuminuria levels with severity of hypertension Study Design: Cross-Sectional Place and Duration: This study was conducted at department of Physiology Basic Medical Sciences Institute in collaboration with Medical ward-7 of Jinnah Post-Graduate Medical Centre, Karachi from January 10, 2005 to June 20, 2005. Subjects and Methods: This study was conducted on 60 subjects classified into following groups. Thirty healthy normal volunteers were studied as control group, (group A). Thirty hypertensive patients included in (group B), were subdivided into B-l (mild hypertensive, Systolic Blood Pressure 140-159mmHg / Diastolic BP 90-99mmHg) and B-2 (moderate hypertensive, SBP 160-179 mmHg / DBP 100-109 mmHg). These sub-groups consisted of 15 subjects each. The parameters included the SBP, DBP, and Mean Arterial Pressure, urinary albumin excretion. Clinical details were collected and 24 hours urinary collection in the container from all the selected subjects were received in the next morning. Results: Analysis of results revealed excretion of albumin to be 55.96 ±10.8 µg/min in group B (hypertensive), in comparison to 14.18 ±0.59 in control group. While in the subgroups of group B, we observed the mean values of urinary albumin excretion 48.93 ±11.72 in subgroup B-l (mild hypertensive), and 63.00 ±18.38 in subgroup B-2 (moderate hypertensive). Conclusion: Our study concluded that increased levels of microalbuminuria are associated with the increasing intensity of hypertension. Early detection of risk factors and timely intervention may ensure a longer and healthier life.